Establishing catheter-related bloodstream infection surveillance to drive improvement. Issue 4 (July 2018) - Hallam, Carole; Jackson, Tim; Rajgopal, Anu; Russell, Belinda
Background: Catheter-related blood stream infections (CRBSI) are an important complication of central venous access devices but are often poorly measured. This article describes the journey of one hospital trust to set up a surveillance process for CRBSI across all specialties of the trust and to reduce CRBSI. Method: Using a locally adapted CRBSI criteria and root cause analysis (RCA) for investigation we identified a number of opportunities for a quality improvement programme. Findings: Over a 5-year period we saw a significant and sustained reduction in the rate of CRBSI from 5 per 1000 catheter days to 0.23 per 1000 catheter days. Conclusions: The surveillance enabled rates of CRBSI to be monitored across the trust and the success of our improvements to be measured.